Node status detection and information diffusion in router network using scale-free network - Mahesar, Abdul Waheed; Messikh Azeddine, Azeddine; Shah, Asadullah; Wahiddin, Mohamed Ridza (Plymouth University, 2014)
In the field of computer networks various routing and inter networking algorithms and protocols have been introduced according to many performance metrics like network topology, scalability, speed, and congestion control requirements. In this paper we have used the concept of scale-free network theory to design a more robust data dissemination approach which can be used in one dynamical Autonomous Systems (AS) to know the appearance and disappearance of nodes, and speedily propagate the information to all nodes in the routers network. By taking advantage of the features of scale-free network behavior as found inhomogeneous structure, short path lengths, highly cluster and epidemiological spreading an enhanced algorithm has been introduced which effectively finds the node status in the network and speedily broadcasts the information of status to all nodes in the network.